'A Man Obscurely Situated': Samuel Richardson, Autobiography and 'The History of Mrs Beaumont'. (16th December 2012) - CURRAN, LOUISE
Abstract This article considers Samuel Richardson's final fictional work, 'The History of Mrs Beaumont', a story removed from his last published novel, Sir Charles Grandison (1753‐4), that now survives in manuscript form (following partial publication in 1804). It explores Richardson's interest in different forms of life‐writing, draws attention to the quasi‐autobiographical nature of this work and argues that 'Mrs Beaumont' demonstrates a new interest in the way personal history could be used in fictional practice. The article concludes that, though fragmentary and neglected by critics to date, the work is a significant part of the novelist's literary oeuvre.